Social Characteristics and Differences of Urban and Rural Communities - Tahmina Yahya; Sulemani Yahya (Borong Newinera Publisher, 2020)
The study aims at describing urban communities and rural communities. A village community is a society whose inhabitants enjoy a major source of livelihood in the agriculture, fishing, livestock sector, or a combination thereof, and whose cultural and social systems support these livelihoods. The characteristics of village communities include the general life order of the group based on kinship. Meanwhile, the urban community is an association of people who live in the center of economic activity, government, arts, science and so on. Urban people seek their livelihoods on average using sophisticated technology, such as using machine power, computers and others.